Хэлийг бүртгэн баримтжуулах нь: Registering and documenting the languages - Ya., Badamsuren (Mongolian Journal of Foreign Languages and Cultures, 2023)
Зохиогч энэхүү өгүүллээрээ дэлхий дахинд буй цөөнх үндэстний хэл, соёлыг хамгаалахын тулд олон улсын байгууллагууд болоод улс гүрнүүд хэл соёлоо хэрхэн баримтжуулж, хойд үедээ өвлүүлдэг талаар мэдээлэхийг зорьсон болно. In the article the author tried to introduce what is language documentation, what organizations are documenting the languages, what for? and the result of language documentation. Language documentation is appeared related to language endangerment and it is very important to save languages from death.